2013
DOI: 10.1080/09205063.2013.830913
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of poly (ϵ-caprolactone) microfiber scaffolds with varying topography and mechanical properties for stem cell-based tissue engineering applications

Abstract: Abstract.Highly porous poly (ε-caprolactone) microfiber scaffolds can be fabricated using electrospinning for tissue engineering applications. Melt electrospinning produces such scaffolds by direct deposition of a polymer melt instead of dissolving the polymer in a solvent as performed during solution electrospinning. The objective of this study was to investigate the significant parameters associated with the melt electrospinning process that influence fiber diameter and scaffold morphology, including process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 48 publications
1
92
0
1
Order By: Relevance
“…Even though there are numerous studies on the fabrication of fibers through the use of solution electrospinning, few studies focus on controlling topographical properties of melt electrospun fibers including the uniform distribution of fiber's diameter and also the architecture of scaffolds. Hohman et al have worked on the modeling of electrospun polymeric fibers [3,29,30]. They have reported that the electrospinning jet is actually pulled along by surface stresses, electrical and elastic forces.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Even though there are numerous studies on the fabrication of fibers through the use of solution electrospinning, few studies focus on controlling topographical properties of melt electrospun fibers including the uniform distribution of fiber's diameter and also the architecture of scaffolds. Hohman et al have worked on the modeling of electrospun polymeric fibers [3,29,30]. They have reported that the electrospinning jet is actually pulled along by surface stresses, electrical and elastic forces.…”
Section: Discussionmentioning
confidence: 99%
“…where, the density of the material(PCL) [3], the jet mass at time , and the charge on the jet ( ) [27] are given as :…”
Section: The Forces Action On the Straight Jetmentioning
confidence: 99%
See 3 more Smart Citations